Uji Sitotoksik Ekstrak Daun Murbei (Morul Alba L) Terhadap Sel Kanker Mcf-7 Dan Selektifitasnya - lukman, Lukman; Marwati, Marwati; Mus, Suwahyuni; Syahruni, Reny (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2021)
Mulberry, Morus alba L., is traditionally used to treat various diseases such as bacterial, fungal, and protozoal. In addition, the society in South Sulawesi uses mulberry leaves as an anti-cancer. The present study aimed to investigate the cytotoxic effect of mulberry leaf extract on breast cancer cells MCF-7 and their selectivity against Vero normal cells. The dried mulberry leaves were extracted by maceration using 96% ethanol. The cytotoxic activity was determined using MTT method, while the selectivity index (SI) was calculated by comparing IC50 of MCF-7 cells against Vero cells. The results showed that the ethanol extract of mulberry leaves was toxic to MCF-7 cells with an IC50 of 75.32±2.78 µg/mL and also toxic to Vero cells (71.73±4.39 µg/mL). However, ethanol extract of mulberry leaves was not selective on MCF-7 cells with an SI value of 0.95. Our study indicates that mulberry could be considered an effective agent in the prevention of cancer, but further studies are necessary needed for safety assessment.